2005
DOI: 10.1007/s00277-005-1064-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among serum leptin levels, complete blood count parameters and peripheral CD34(+) cell count in prepubertal obese children

Abstract: Leptin is a hormone produced by adipocytes that helps reduce body weight by depressing appetite and increasing metabolic activity. Leptin also promotes early hematopoiesis. The main aim of this study was to compare complete blood count (CBC) parameters and peripheral blood CD34(+) cell counts in prepubertal obese and nonobese children. Relationships between leptin levels and CBC parameters and peripheral CD34(+) progenitor cell counts in the obese group were also investigated. Thirty one healthy, prepubertal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…In contrast, antioxidant activities of superoxide dismutase, glutathione peroxidase, and IL-2 are decreased (Aygun et al, 2005;Martos et al, 2006;Ustundag et al, 2007;Olza et al, 2010). However, high leptin levels in childhood obesity do not seem to be associated with altered complete blood count parameters or increased peripheral CD34(+) progenitor cell count (Kinik et al, 2005).…”
Section: Introductionmentioning
confidence: 80%
“…In contrast, antioxidant activities of superoxide dismutase, glutathione peroxidase, and IL-2 are decreased (Aygun et al, 2005;Martos et al, 2006;Ustundag et al, 2007;Olza et al, 2010). However, high leptin levels in childhood obesity do not seem to be associated with altered complete blood count parameters or increased peripheral CD34(+) progenitor cell count (Kinik et al, 2005).…”
Section: Introductionmentioning
confidence: 80%
“…Our previous findings showed that blocking megalin expression in the choroid plexus cells resulted in lower leptin levels in the cerebrospinal fluid caused by impairments in the leptin transport [ 3 ]. Significantly high serum leptin levels were presented in obese subjects compared to a healthy control population suggesting the leptin resistance as the main risk factor to induce obesity [ 20 , 21 ]. Studies showed that endothelial specific leptin receptor knockout elicits persistent leptin transport even increasing the leptin uptake into the brain parenchyma [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naimi (2003) showed that endurance exercises have no significant effect on heart rate (17). On the other hand, some other studies have found a relationship between hematological parameters and Body Mass Index (BMI) in obese adolescents (18,19). Hematological parameters, especially red blood cells and hemoglobin are responsible for carrying nutrients and oxygen to active tissues and excretion of waste and carbon dioxide from tissues to lungs.…”
Section: Introductionmentioning
confidence: 99%